2015
DOI: 10.1148/radiol.2015142366
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Molecular Features of Hepatocellular Adenoma with Gadoxetic Acid–enhanced MR Imaging

Abstract: Purpose:To evaluate the diagnostic performance of imaging features of gadoxetic acid-enhanced magnetic resonance (MR) imaging to differentiate among hepatocellular adenoma (HCA) subtypes by using the histopathologic results of the new immunophenotype and genotype classification and to correlate the enhancement pattern on the hepatobiliary phase (HBP) with the degrees of expression of organic anion transporting polypeptide (OATP1B1/3), multidrug resistance-associated protein 2 (MRP) (MRP2), and MRP 3 (MRP3) tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…These findings, even if based on a relatively limited number of observations, suggest that signal intensity may be a surrogate marker of OATPB1/B3 presence or loss. In agreement with our results, Ba‐Ssalamah et al reported Gd‐EOB‐DTPA “retention” in 83% of b‐HCA on the HBP of Gd‐EOB‐DTPA‐enhanced MRI, while they inconsistently observed this hyperintensity in other HCA subtypes . However, this series did not include all subtypes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings, even if based on a relatively limited number of observations, suggest that signal intensity may be a surrogate marker of OATPB1/B3 presence or loss. In agreement with our results, Ba‐Ssalamah et al reported Gd‐EOB‐DTPA “retention” in 83% of b‐HCA on the HBP of Gd‐EOB‐DTPA‐enhanced MRI, while they inconsistently observed this hyperintensity in other HCA subtypes . However, this series did not include all subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies aimed to elucidate this phenomenon, showing mostly a hypointense profile . In a recent radio‐pathological report, it has been suggested that, in HCA, the degree of OATPB1/B3 and MRP3 expression correlated, respectively, with Gd‐EOB‐DTPA “retention” and “washout” seen on HBP MR images . However, a precise pathological characterization of HT expression patterns in HCA subtype according to the most recent classification, particularly in HCA with less common phenotypes (atypical H‐HCA, ASS1+HCA), and with higher risk of malignant transformation (b‐IHCA, b‐HCA) and HCA‐HCC, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although not all included lesions were confirmed by pathology, most of the discrepancies occurred in inflammatory subtype HCAs. Furthermore, in addition to the fact that these lesions can be intrinsically hyperintense, they may take up contrast in the HBP to a certain degree . This characteristic might go some way to explaining why inflammatory HCAs in our study population were more often iso‐ to hyperintense in the HBP using Gd‐BOPTA.…”
Section: Discussionmentioning
confidence: 86%
“…First, it could be related to OATP1B1/3 and MRP3 expression. OATP1B1/3 could affect Gd-EOB-DTPA uptake by HCA cells, while MRP3 affects its excretion from the same cells; therefore, OATP1B1/3 and MRP3 levels, which vary substantially in different HCA subtypes, could directly affect the intensity of HBP signals 9.Second, fatty degeneration of the liver could also affect the relative intensity of HCA signals in the HBP5. Finally, chronic inflammation could reduce bile duct reactivity 14.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, such scars are very difficult to identify by imaging examinations 26-28. For lesions >3 cm, the central scar could provide some evidence for the differential diagnosis between HCA and FNH, however, in some pathological subtypes of HCA, especially H-HCA, the incidence of scar sign in the lesion may reach 30% 9,11-12.…”
Section: Discussionmentioning
confidence: 99%